Economic Cooperation of Russia and China in the Field of Innovation Infrastructure - Eugenia A. Kuklina; Yuxiu Sun (Евразийская интеграция: экономика, право, политика, 2019)
The relevance of the research of the cooperation between Russia and China in the innovative sphere is due to the necessity to raise competitiveness of both countries, provision their sustainable and dynamic development. The intensification of cooperation in the sphere of innovation is a positive trend in the modern development of Russian-Chinese relations. The article presents the results of researches aimed at analyzing the prospects of economic cooperation between Russia and China in the sphere of innovative infrastructure creation (by the example of technological parks). The research identifies the strategic priorities of science, technology and education in China, formulates the factors of intensification of economic cooperation between Russia and China in creation of technological parks as the most important elements of innovative infrastructure. Moreover the example of the positive experience of realization of the hi-tech park project “The Silk Road” was considered in the article and the results of its activity for cooperation perceptivities in the innovative sphere were evaluated. Eventually the article identified the following positive factors of development of economic cooperation in technological parks creation: the construction Belt and Road, which allows to activate the process of creating infrastructure, energy, communications, production, finance and humanitarian exchanges; positive experience of China in the creation of the free economic zones and technological parks; the successful use of fiscal methods to stimulate innovative activities.